The Effects of Aerobic Sports on Fatigue and Vital Sign in Sportsman - Aditya Candra; Tahara Dilla Santi (Universitas Serambi Mekkah, 2022)
The lactic acid buildup has long been suspected as a cause of muscle fatigue. Lactate is a waste of anaerobic metabolism; this process takes place in the absence of oxygen. Blood pressure, pulse, and respiration are vital signs to monitor adaptation to fatigue levels. This study aims to determine the effect of aerobic exercise on the level of fatigue and vital signs in athletes. This research is a quasi-experimental study with a non-random re-experimental design. Lactic acid levels and vital signs were assessed before and after the exercise program in 3 groups, namely the light-intensity exercise treatment group, the moderate-intensity exercise group, and the control group. The research site is at the Harapan Bangsa football stadium in Banda Aceh. The subject of PPLP Dispora Aceh athletes. The exercise was carried out for four weeks. The average lactic acid levels of the three groups showed differences. A significant decrease in lactic acid after the training test was seen in the group with OAIS (p = 0.04). Exercise with the right intensity, duration, and frequency can reduce lactic acid levels and vital signs. This study shows that moderate-intensity exercise can affect reducing lactic acid levels and vital signs so that it can slow down fatigue during exercise in Aceh football athletes. Keywords: Light and Moderate Intensity Exercise, Lactic Acid, Vital Signs.